2012
DOI: 10.2113/jeeg17.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Collapse Risk in Evaporite Sinkhole-prone Areas Using Microgravimetry and Radar Interferometry

Abstract: Geophysical and remote-sensing methods were applied to better understand sinkhole precursor movement and assess the potential for sinkhole development in evaporitic areas. The approach is illustrated with two examples over bedded salt deposits and a salt dome in Texas, USA. Large sinkholes (90 to 200 m in diameter) formed over Permian bedded salt near Wink in western Texas in June 1980 and May 2002, and on the flank of a coastal-plain salt dome in Daisetta in May 2008. Residents, government officials, and indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 4 publications
(6 reference statements)
1
27
0
Order By: Relevance
“…The maximum subsidence happens in (d) area (d in Figure 4), at a rate of up to ~13 cm/year. Paine et al [16] observed the deformation (green polygon in Figure 4a) in the same area between January and July, 2007. The deforming area has significantly been stretched in dimensions.…”
Section: Observationsmentioning
confidence: 85%
See 2 more Smart Citations
“…The maximum subsidence happens in (d) area (d in Figure 4), at a rate of up to ~13 cm/year. Paine et al [16] observed the deformation (green polygon in Figure 4a) in the same area between January and July, 2007. The deforming area has significantly been stretched in dimensions.…”
Section: Observationsmentioning
confidence: 85%
“…InSAR has been proven to be a powerful tool for monitoring these sinkhole precursors and post-event deformation in the Dead Sea, Israel [8][9][10][11], Bayou Corne, Louisiana, USA [12], New Mexico [13], and Ebro Valley, Spain [14,15]. Ground subsidence around the sinkholes in Wink, Texas, was measured using a single InSAR image, along with field gravity observations by Paine et al [16]. Despite the success of these previous studies, monitoring sinkhole deformation through InSAR techniques is still challenging, due to the low spatial resolution of synthetic aperture radar (SAR) sensors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…of Health, 1998 andWilson, 2012). Nitrate concentrations greater than 3 ppm indicates that an aquifer has been impacted by activities on the land surface (Minn. Dept.…”
Section: Figure 5 2013 Girl Scout Camp Creek Site Sampling Locationsmentioning
confidence: 99%
“…Paine et. alia [6] utilized InSAR in order to find subsiding locations of interest, then deployed microgravity measurements to further characterize those locations. The addition of microgravimetry to finely characterize potential sinkholes is distinct from our study, where we defer to more generalized field verification carried out by a geologist.…”
Section: Insar-based General Detection Of Geohazardsmentioning
confidence: 99%